FORMATION OF MOTIVATIONAL COMPETENCES FOR PROFESSIONAL ACTIVITY IN MASTER STUDENTS OF SPECIALTY 011 - Жиленко, Микола (Київський національний університет імені Тараса Шевченка, 2022)
The article analyzes the requirements of the National Qualifications Framework of Ukraine, the Standard of the second (master's) level of higher education, specialty 011, and the professional standard for the group of professions "Teachers of higher education institutions". The requirements of these documents regarding the formation of competencies and program results of training for masters in the specialty 011 educational, pedagogical sciences, which are related to the readiness of future specialists to rely on the human factor in their activities: the level of qualification, social activity,industrial initiative, professional and general training, are defined. civic responsibility, state of health, physical training of people. It has been clarified to what extent these requirements are reflected in the description of the educational program "Pedagogy of the Higher School", which is implemented at the Department of Pedagogy of Taras Shevchenko Kyiv National University. Competences and program results of training of students of higher education in specialty 011 were ranked and on this basis the place of those related to the ability to motivate participants in the educational process during training and the main types of methodical, scientific and organizational work was determined. The curriculum of the educational program has been analyzed, the educational components have been determined, within the framework of which the formation of motivational competences in the students during the training process should be ensured. An approach to the meaningful filling of the educational components of the educational program is proposed for students to understand the needs, motives, goals and attitudes that contribute to or hinder the formation of the participants of the educational process, first of all, internal motivation, which is a necessary condition for productive activity.

Проаналізовано вимоги Національної рамки кваліфікацій України, Стандарту другого (магістерського) рівня вищої освіти спеціальності 011 і професійного стандарту на групу професій "Викладачі закладів вищої освіти". Визначено вимоги цих документів щодо формування компетентностей і програмних результатів навчання у магістрів спеціальності 011 Освітні, педагогічні науки, які пов'язані з готовністю майбутніх фахівців у своїй діяльності спиратися на людський фактор: рівень кваліфікації, соціальну активність, виробничу ініціативу, професійну й загальну підготовку, громадянську відповідальність, стан здоров'я, фізичну підготовку. З'ясовано, якою мірою ці вимоги відображено в описі освітньої програми "Педагогіка вищої школи", що реалізується на кафедрі педагогіки Київського національного університету імені Тараса Шевченка. Проведено ранжування компетентностей і програмних результатів навчання здобувачами вищої освіти спеціальності 011 і на цій основі визначено місце тих, що пов'язані зі здатністю мотивувати учасників освітнього процесу під час навчальної та основних видів методичної, наукової й організаційної роботи. Проаналізовано навчальний план освітньої програми, визначено освітні компоненти, у межах яких має бути забезпечене формування мотиваційних компетентностей у здобувачів під часнавчання. Запропоновано підхід до змістового наповнення освітніх компонентів освітньої програми для розуміння здобувачами місця потреб, мотивів, цілей і настанов, що сприяють або перешкоджають формуванню в учасників освітнього процесу передусім внутрішньої мотивації, яка є обов'язковою умовою продуктивної діяльності.
ФОРМУВАННЯ В МАГІСТРАНТІВ СПЕЦІАЛЬНОСТІ 011 МОТИВАЦІЙНИХ КОМПЕТЕНТНОСТЕЙ ДЛЯ ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ